Development of Islamic Education Textbooks Based on Contextual Teaching and Learning to Reduce Student Difficulties - Sakinah, Aini; Pohan, Ali Jusri; Pratami, Fuji (Ahlussunnah: Journal of Islamic Education, 2025)
The development of Islamic Education textbooks based on Contextual Teaching and Learning is designed to bridge the academic world with the realities of students' lives. With this approach, religious material becomes more meaningful and can reduce students' difficulties in understanding Islamic values. This study aims to create an Islamic Education textbook that uses the Contextual Teaching and Learning approach, which addresses learning difficulties. The method used is the Four-D model, which consists of four stages, namely Define, Design, Develop, and Disseminate. The results of the validators' validation of the media and material are divided into two parts, namely that the open book on Islamic Education has very high validity with a percentage. Meanwhile, the open book on Islamic Religious Education based on Contextual Teaching and Learning has very high validity. Regarding the practicality of the open book on Islamic Religious Education based on Contextual Teaching and Learning, based on the answers of teachers who teach this subject, the percentage reached 83.75%, which is classified as very practical. Meanwhile, their responses regarding the practicality of the open book on Islamic Religious Education based on Contextual Teaching and Learning reached 87.87%, which is classified as very practical. By developing textbooks on Islamic Religious Education based on Contextual Teaching and Learning, the teaching materials become closer to the daily experiences of students, so that abstract concepts feel more real and easier to understand. This approach also increases student engagement in learning because they can see the relevance of Islamic values in their lives, which ultimately reduces the difficulty in understanding and internalizing religious teachings